FEATURES OF CURRICULUM DEVELOPMENT IN THE MANAGEMENT OF AN EDUCATIONAL INSTITUTION - Ustajalilova Khurshida Alievna,; Turginbaeva Ardak Nesipbekovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article shows the peculiarities of curriculum development in the management of an educational institution, the dependence of the quality of education and training, as well as the training of competitive personnel on the correct choice of disciplines, the volume of the academic load, the organization of the learning trajectory. The role of information technologies, the electronic management system, the issue of material and technical support of the management system is shown, which can be resolved if there is an effectiveness of the proposed developments for the development of the education sector, as well as beneficial for the state, which invests in an educational institution. In addition, the optimization of subjects, the formation of modern content and resources is important when managing what students are expected to learn, developing criteria for assessing whether it has been learned and finding ways to improve student learning.